2013
DOI: 10.1136/bcr-2013-010382
|View full text |Cite
|
Sign up to set email alerts
|

Giant pilomatricoma in a patient with tuberous sclerosis, both diagnosed in the adult life

Abstract: Pilomatricoma is a relatively common benign skin neoplasm originating from the hair follicle matrix cells. β-Catenin is a subunit of the cadherin protein complex. It acts as an intracellular signal transducer that influences cell differentiation and proliferation. This protein was recently involved in the formation of hair follicle-related tumours, including pilomatricomas. Tuberous sclerosis (TS) is an inherited neurocutaneous disease, which is characterised by pleomorphic features involving many organs, hama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Pilomatrixoma is only rarely diagnosed in the phacomatoses: A report describes the diagnosis of a pilomatrixoma associated with the initial diagnosis of tuberous sclerosis (14). Another report is on the diagnosis of pilomatrixoma associated with a case of multiple epidermal nevi (15).…”
Section: Discussionmentioning
confidence: 99%
“…Pilomatrixoma is only rarely diagnosed in the phacomatoses: A report describes the diagnosis of a pilomatrixoma associated with the initial diagnosis of tuberous sclerosis (14). Another report is on the diagnosis of pilomatrixoma associated with a case of multiple epidermal nevi (15).…”
Section: Discussionmentioning
confidence: 99%
“…Tuberous sclerosis is a disorder involving the formation of hamartomas in multiple organ systems, particularly in the brain, skin, heart, lungs, and kidney (Nguefack et al, 2012;Resende et al, 2013). Studies have identified the TSC1 gene, located on 9q34 (Fryer et al, 1987), as the etiological culprit in this disease.…”
Section: The Structure and Activity Of Hamartinmentioning
confidence: 99%
“…An association between pilomatricoma and some genetic conditions has been suggested, with tumorigenesis linked to genes responsible for these genetic conditions via beta-catenin regulation in the Wnt signaling pathways. A number of patients with pilomatricoma(s) in the presence of concurrent genetic conditions have been reported, including Gardner syndrome [ 2 4 ], Rubinstein-Taybi syndrome [ 5 10 ], myotonic dystrophy [ 11 – 16 ], Turner syndrome [ 17 22 ], Kabuki syndrome [ 23 , 24 ], tuberous sclerosis [ 25 , 26 ], constitutive mismatch repair deficiency [ 27 ], Sotos syndrome [ 28 , 29 ], neurofibromatosis I [ 30 ], Stickler syndrome [ 22 ], MYH-associated polyposis [ 31 ], partial trisomy 9 [ 32 ], and tetrasomy 9p syndrome [ 33 , 34 ]. The CTNNB1 gene (OMIM∗116806) on chromosome 3p22.1 encodes beta-catenin, a 92 kD cytoplasmic protein that plays an important role in the creation and maintenance of epithelial cell layers by regulating cell growth and adhesion between cells.…”
Section: Introductionmentioning
confidence: 99%
“…Kabuki syndrome [23,24], tuberous sclerosis [25,26], constitutive mismatch repair deficiency [27], Sotos syndrome [28,29], neurofibromatosis I [30], Stickler syndrome [22], MYH-associated polyposis [31], partial trisomy 9 [32], and tetrasomy 9p syndrome [33,34]. The CTNNB1 gene (OMIM * 116806) on chromosome 3p22.1 encodes betacatenin, a 92 kD cytoplasmic protein that plays an important role in the creation and maintenance of epithelial cell layers by regulating cell growth and adhesion between cells.…”
Section: Introductionmentioning
confidence: 99%